Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper examines inflation dynamics over the past five years for Lithuania. A decomposition of inflation into its components provides clues to its main causes. It shows that energy price increases and convergence to European Union (EU)-wide price levels have been important factors driving inflation, but domestic demand pressures-and wage growth, in particular-have also contributed to inflation. The types of possible efficiency gains are illustrated in the context of health care and social assistance. The paper also examines migration and its long-term fiscal implications.